An updated survey of beliefs and practices related to faking in individual assessments. (31st May 2021) - Robie, Chet; Risavy, Stephen D.; Jacobs, Rick R.; Christiansen, Neil D.; König, Cornelius J.; Speer, Andrew B.
Abstract: The present study is an updated survey examining individual assessor beliefs and practices related to faking in the individual assessment context. The responses from a mix of quantitative and qualitative survey questions were compared across individual assessors from the original 2005 sample ( n = 77) and an updated 2020 sample ( n = 78). Results suggest that single stimulus personality assessments are still the predominant form of personality assessment in use, but many individual assessors employ other types of personality assessments such as forced‐choice. In 2020, individual assessors do not appear to be heavily concerned about the effects of faking on their recommendations, do not believe that a large number of candidates fake, and believe that even fewer candidates successfully fake.